PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE (TPS) KELAS VI SDN 001 EMPAT BALAI KECAMATAN KUOK KABUPATEN KAMPAR - Maznah ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this research is the lack of students' mathematics learning outcomes. Thiscan be seen from 28 students only 13 students reaching 46.43% KKM. In addition, theaverage value is obtained by the students was 56.96. This research is a classroom actionresearch (PTK), the research was conducted SDN 001 Empat Balai Kecamatan Kouk. Thisresearch was conducted in two cycles by applying the model TPS learners. The purpose ofthis study is to improve students' mathematics learning outcomes. The data used in this studyis the result of learning and activity data of teachers and students. The study states that theTPS learning model can improve the results of math students learn some vital lessons. This isevidenced by: (a) the learning outcomes of students has increased at each cycle. At the basescore is the average value obtained was 56.96 by the number of students who completed 13(46.43%). In the first cycle the average value of the acquisition was 69 with the number ofstudents who completed was 19 (69.86%). In the second cycle of acquisition the averagevalue obtained was 77.43 students complete student number was 24 (85.71%); and (b) theactivities of teachers has increased in each cycle, the first cycle 1 meeting obtain a score of14 (58.33%) with less category, the first cycle 2 meeting obtain a score of 16 (66.67%) withenough categories, in cycle II meeting 1 given a score of 19 (79.16%) in both categories. Andthe second cycle 2 meeting obtain a score of 21 (87.50%) with a very good category. And thestudents' activity has increased in the first meeting of the first cycle of activity students obtaina score of 13 (54.16 %%) with less category, the second meeting of the second cycle obtain ascore of 16 (66.67%) with enough categories, the first meeting of the second cycle obtain ascore of 18 (75.00%) in both categories. And at the second meeting of the second cycle obtaina score of 22 (91.67%) with a frightening good category.